Sex differences in endovascular thrombectomy outcomes in large vessel occlusion: a propensity-matched analysis from the SELECT study. (1st March 2022) - Fifi, Johanna T; Nguyen, Thanh N; Song, Sarah; Sharrief, Anjail; Pujara, Deep Kiritbhai; Shaker, Faris; Fournier, Lauren E; Jones, Erica M; Lechtenberg, Colleen G; Slavin, Sabreena J; Ifejika, Nneka L; Diaz, Maria V; et al.
Abstract : Background: Sex disparities in acute ischemic stroke outcomes are well reported with IV thrombolysis. Despite several studies, there is still a lack of consensus on whether endovascular thrombectomy (EVT) outcomes differ between men and women. Objective: To compare sex differences in EVT outcomes at 90-day follow-up and assess whether progression in functional status from discharge to 90-day follow-up differs between men and women. Methods: From the Selection for Endovascular Treatment in Acute Ischemic Stroke (SELECT) prospective cohort study (2016–2018), adult men and women (≥18 years) with anterior circulation large vessel occlusion (internal carotid artery, middle cerebral artery M1/M2) treated with EVT up to 24 hours from last known well were matched using propensity scores. Discharge and 90-day modified Rankin Scale (mRS) scores were compared between men and women. Furthermore, we evaluated the improvement in mRS scores from discharge to 90 days in men and women using a repeated-measures, mixed-effects regression model. Results: Of 285 patients, 139 (48.8%) were women. Women were older with median (IQR) age 69 (57–81) years vs 64.5 (56–75), p=0.044, had smaller median perfusion deficits (Tmax >6 s) 109 vs 154 mL (p<0.001), and had better collaterals on CT angiography and CT perfusion but similar ischemic core size (relative cerebral blood flow <30%: 7.6 (0–25.2) vs 11.4 (0–38) mL, p=0.22). In 65 propensity-matched pairs, despite similar discharge functional independence rates (women: 42% vs men: 48%, aOR=0.55, 95% CI 0.18 to 1.69, p=0.30), women exhibited worse 90-day functional independence rates (women: 46% vs men: 60%, aOR=0.41, 95% CI 0.16 to 1.00, p=0.05). The reduction in mRS scores from discharge to 90 days also demonstrated a significantly larger improvement in men (discharge 2.49 and 90 days 1.88, improvement 0.61) than in women (discharge 2.52 and 90 days 2.44, improvement 0.08, p=0.036). Conclusion: In a propensity-matched cohort from the SELECT study, women had similar discharge outcomes as men following EVT, but the improvement from discharge to 90 days was significantly worse in women, suggesting the influence of post-discharge factors. Further exploration of this phenomenon to identify target interventions is warranted. Trial registration number: NCT02446587 .